Supply Chain Performance Management Strategy in Improving Supply Chain Performance Competitiveness of Special Product at Indomaret Fresh Bekasi Branch - Melenneta Aisyah Putri Melenneta; Muhammad Iqbal Firdaus; Euis Saribanon (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2025)
This study analyzes the influence of supply chain knowledge capability, information sharing capability, and supply chain collaboration capability on supply chain performance and competitiveness at the Indomaret Fresh Bekasi Branch. The research is grounded in the Resource-Based View (RBV) and applies the VRIO framework to evaluate whether these capabilities constitute sources of competitive advantage. A quantitative research design was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through questionnaires distributed to 102 employees across 14 Indomaret Fresh outlets in Bekasi. The results demonstrate that supply chain knowledge capability and supply chain collaboration capability have a significant positive effect on supply chain performance. Collaboration capability also shows a direct and significant effect on supply chain competitiveness, while supply chain knowledge influences competitiveness indirectly through supply chain performance. In contrast, information sharing capability does not have a significant direct effect on either supply chain performance or competitiveness, although it remains operationally important for coordination and efficiency. Supply chain performance plays a crucial mediating role by strengthening the relationship between supply chain capabilities, particularly knowledge and collaboration, and supply chain competitiveness. The VRIO analysis reveals that supply chain collaboration fulfills all criteria of valuable, rare, inimitable, and well-organized resources, making it a sustainable source of competitive advantage. Supply chain knowledge is valuable and well-organized but not rare, resulting in a temporary competitive advantage. Information sharing, while necessary for operational effectiveness, does not meet VRIO criteria as a strategic resource. This study contributes to the literature by integrating RBV, VRIO, and SEM-PLS in the context of fresh product retail supply chains. Practically, the findings emphasize the importance of strengthening collaborative practices and optimizing supply chain performance to enhance competitiveness in highly competitive urban retail markets.